2004
DOI: 10.1007/bf03217706
|View full text |Cite
|
Sign up to set email alerts
|

Retreatment of patients with chronic hepatitis C not responding to interferon/ribavirin combination therapy with daily interferon plus ribavirin plus amantadine

Abstract: There is currently no accepted therapeutic regimen for patients with chronic hepatitis C who failed to respond to standard combination treatment with interferon-alpha plus ribavirin. We investigated triple combination treatment with induction dosing of interferon-alpha plus ribavirin plus amantadine in these difficult-to-treat patients. Nonresponders (n = 67), breakthroughs (n = 16) and relapsers (n = 19) to previous interferon/ribavirin combination treatment of at least 6 months were included. For the first 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…In previously untreated patients, the addition of amantadine has either improved the outcomes of interferon monotherapy [2,3] or has had no beneficial effect [4][5][6][7]. Although meta-analysis data indicate that interferon plus amantadine therapy may be an alternative regimen for patients who cannot tolerate ribavirin [8], the efficacy of triple therapy, both as initial therapy or for the treatment of non-responders to interferon plus ribavirin, is uncertain [9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In previously untreated patients, the addition of amantadine has either improved the outcomes of interferon monotherapy [2,3] or has had no beneficial effect [4][5][6][7]. Although meta-analysis data indicate that interferon plus amantadine therapy may be an alternative regimen for patients who cannot tolerate ribavirin [8], the efficacy of triple therapy, both as initial therapy or for the treatment of non-responders to interferon plus ribavirin, is uncertain [9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of triple combination therapy regimens, whereby a third agent with a different mode of action is added to standard therapy, has recently been assessed among previous non-responders and those with 'difficult to treat' characteristics. Studies using a triple combination with amantadine (an antiviral agent) have generally shown a modest or no added benefit compared with standard therapy [29,30,[81][82][83][84]. However, a recent meta-analysis of 38 randomized studies suggested some benefit in previous non-responders, but no notable effect in treatment-naive or relapser patients [27].…”
Section: Retreatment With Other Drug Combinationsmentioning
confidence: 99%
“…Standard IFN-a, although less efficacious than pegylated IFN, allows better control of platelet and white blood cell counts, because of different pharmacokinetics with a shorter half-life. In previous studies, daily administration of IFN was well tolerated [18]. Thus, therapy with low-dose standard IFNs with a later dose increase -an 'accelerating dose regimen' [19] -may be beneficial in the setting of these difficult-to-treat patients with cirrhosis.…”
Section: Introductionmentioning
confidence: 97%